S-allylmercaptocysteine inhibits TLR4-mediated inflammation through enhanced formation of inhibitory MyD88 splice variant in mammary epithelial cells - Miyuki Takashima; Masahiro Kurita; Haruhi Terai; Feng-Qi Zhao; Jun-ichiro Suzuki (Scientific Reports)
Abstract Mastitis is an inflammatory disease affecting mammary tissues caused by bacterial infection that negatively affects milk quality and quantity. S-Allylmercaptocysteine (SAMC), a sulfur compound in aged garlic extract (AGE), suppresses lipopolysaccharide (LPS)-induced inflammation in mouse models and cell cultures. However, the mechanisms underlying this anti-inflammatory effect remain unclear. In this study, we demonstrated that oral administration of AGE suppressed the LPS-induced immune response in a mastitis mouse model and that SAMC inhibited LPS-induced interleukin-6 production and nuclear factor κB p65 subunit activation in HC11 mammary epithelial cells. Global phosphoproteomic analysis revealed that SAMC treatment downregulated 910 of the 1,304 phosphorylation sites upregulated by LPS stimulation in mammary cells, including those associated with toll-like receptor 4 (TLR4) signaling. Additionally, SAMC decreased the phosphorylation of 26 proteins involved in pre-mRNA splicing, particularly the U2 small nuclear ribonucleoprotein complex. Furthermore, we found that SAMC increased the production of the myeloid differentiation factor 88 short form (MyD88-S), an alternatively spliced form of MyD88 that negatively regulates TLR4 signaling. These findings suggest that SAMC inhibits TLR4-mediated inflammation via alternative pre-mRNA splicing, thus promoting MyD88-S production in mammary epithelial cells. Therefore, SAMC may alleviate various inflammatory diseases, such as mastitis, by modulating immune responses.